Implementasi Sistem Informasi Manajemen Dalam Mendukung Pelayanan Administrasi - Azizah, Mar'atul; Solikhin, Solikhin; Lailiyah, Nurul (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study examines the implementation of Management Information Systems (MIS) in supporting administrative services at MA Miftahul Ulum Cermenan Ngoro Jombang. Using a qualitative descriptive approach, the research explores the complexities and dynamics of MIS implementation in an Islamic educational context. Data was collected through in-depth interviews, direct observations, and document analysis. The findings reveal significant progress in integrating information technology into various aspects of educational management and services, including teaching, administration, and facility management. The madrasah has demonstrated a commitment to improving operational efficiency and educational service quality through technological innovation. However, challenges persist, including gaps between planning and implementation, the need for IT infrastructure development, and human resource capacity building. In the context of Islamic education, MIS implementation opens opportunities to strengthen Islamic values and principles through technology while maintaining the essence of human interaction in education. The study concludes that successful MIS implementation at MA Miftahul Ulum depends on the institution's ability to address existing challenges, maintain focus on core educational objectives, and continuously adapt to evolving technological and educational needs. With a holistic and strategic approach, MA Miftahul Ulum has the potential to become a model of excellence in integrating modern technology with traditional Islamic educational values, creating an innovative and relevant learning environment in the digital era